Assessment of enthesitis in ankylosing spondylitis. Issue 2 (1st February 2003) - Heuft-Dorenbosch, L; Spoorenberg, A; van Tubergen, A; Landewé, R; van der Tempel, H; Mielants, H; Dougados, M; van der Heijde, D
Abstract : Objective: To assess, firstly, the validity of the enthesis index published by Mander (Mander enthesis index (MEI)) and, secondly, to investigate whether it is possible to define a new enthesis index that is less time consuming to perform with at least similar or better properties. Methods: Data from the OASIS cohort, an international, longitudinal, observational study on outcome in ankylosing spondylitis, were used. In this study, measures of disease activity, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the MEI, were assessed regularly in 217 patients. With the MEI, for each measurement period independently, a process of data reduction was performed to identify the entheses most commonly reported as painful by the patients. A more concise enthesis index was constructed with aid of the entheses found in this way. Correlations with measures of disease activity were used to test the validity of several entheses indices. Results: Reduction of the number of entheses from 66 to 13 and omitting grading of the intensity of pain resulted in an index which was named the "Maastricht Ankylosing Spondylitis Enthesitis Score" (MASES). The MASES (range 0–13) has much greater feasibility than the MEI (range 0–90). However, up to 21% of patients with a score >0 on the MEI were not identified by a score on the MASES >0. Only 2.1% of the patients with an original enthesis score >0 had an original score on the MEI >3 (range 0–90) and it can be questioned whether a low score on the MEI index represents clinically important enthesitis. The Spearman correlation coefficient between the MASES score and the MEI was 0.90 and between the MASES and the BASDAI was 0.53 compared with a correlation of 0.59 between the MEI and the BASDAI. Conclusions: MASES seems to be a good alternative to the MEI with much better feasibility.